2017
DOI: 10.3390/toxins9070205
|View full text |Cite
|
Sign up to set email alerts
|

Biooxidation of Ciguatoxins Leads to Species-Specific Toxin Profiles

Abstract: Ciguatoxins (CTXs) contaminate fish worldwide and cause the foodborne illness ciguatera. In the Pacific, these toxins are produced by the dinoflagellate Gambierdiscus toxicus, which accumulates in fish through the food chain and undergoes oxidative modification, giving rise to numerous analogs. In this study, we examined the oxidation of CTXs in vitro with liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis using reference toxins, and found that CTX4A, CTX4B, and CTX3C, which are produced by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 28 publications
4
75
1
Order By: Relevance
“…These cyclic polyether neurotoxins are among the five most potent natural toxins isolated to date [4]. Because they accumulate in coral reef fish, they can be transferred through the marine food web [5][6][7][8]. In fact, CTXs are the main toxins responsible for ciguatera fish poisoning (CFP) [9], a clinical syndrome caused by eating CTX-contaminated fish.…”
Section: Introductionmentioning
confidence: 99%
“…These cyclic polyether neurotoxins are among the five most potent natural toxins isolated to date [4]. Because they accumulate in coral reef fish, they can be transferred through the marine food web [5][6][7][8]. In fact, CTXs are the main toxins responsible for ciguatera fish poisoning (CFP) [9], a clinical syndrome caused by eating CTX-contaminated fish.…”
Section: Introductionmentioning
confidence: 99%
“…CP is endemic in temperate waters of the Pacific Ocean and Caribbean Sea and was recently detected in the Northeast Atlantic [2][3][4][5][6]. A main difficulty in advancing CP research is the lack of reference materials of these toxins and the numerous toxic analogues present in the toxic samples [7,8]. This lack of reference materials limits progress in method development and identification of CTX analogues responsible for the CP.…”
Section: Introductionmentioning
confidence: 99%
“…Roeder et al (2010) [69] reported that 2,3-dihydroxy-P-CTX-3C was produced by G. australes, G. carpenteri, G. caribaeus, G. pacificus, and G. toxicus. It is noted that this analogue is considered a fish metabolite and not produced by the dinoflagellates [70].…”
Section: Ciguatera Fish Poisoning Related Toxins and Their Toxicitymentioning
confidence: 99%